2021
DOI: 10.3389/fvets.2020.588749
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare of Beef Cattle in the Scientific Literature From 1990 to 2019: A Text Mining Approach

Abstract: Beef cattle are the third most numerous terrestrial farmed animals worldwide. Factors such as geographical region, animal category, breed, and rearing system pose specific animal welfare challenges that can have an impact on animal and public health. This article uses text mining (TM) and topic analysis (TA) to explore the scientific literature on beef cattle welfare published in English from 1990 to 2019. Our aim was to reveal the main research topics and their evolution over time. Our analysis showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 86 publications
0
9
0
1
Order By: Relevance
“…La mortalidad de las crías en sistemas de producción bovina, tanto de lechería especializada como de cría, es considerado un problema e indicador de bienestar, debido a que se asocia con una pobre calidad de vida y de sufrimiento (Costa et al, 2019;Nalon et al, 2021). Se estima que la tasa de mortalidad de terneros al destete en sistemas de leche y de carne es hasta 10% (Mee, 2020).…”
Section: Discussionunclassified
“…La mortalidad de las crías en sistemas de producción bovina, tanto de lechería especializada como de cría, es considerado un problema e indicador de bienestar, debido a que se asocia con una pobre calidad de vida y de sufrimiento (Costa et al, 2019;Nalon et al, 2021). Se estima que la tasa de mortalidad de terneros al destete en sistemas de leche y de carne es hasta 10% (Mee, 2020).…”
Section: Discussionunclassified
“…Then, the resulting topics were ranked according to the cumulative probability of the first 15 words of each topic. The individual topics were visualized in a bar histogram representation with the probabilities of the first 15 words within each topic (beta values) and the authors attributed a name to each topic as suggested in the literature ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…A term frequency-inverse document frequency (TF-IDF) technique was applied to weight the number of times a word stem appeared across titles, abstracts, and keywords of the selected records. A research area modelling analysis was carried out using latent Dirichlet allocation (LDA) to generate research theme representations according to the frequency distribution of word stems within titles, abstracts, and keywords via an iterative probabilistic process using a Gibbs sampling option of the research area models package in R. The five generated research themes based on the ten most probable word stems were presented as an unstructured set of word stems using histograms, where every bar representing each word stem is proportional to the probability (beta value) of finding it in a theme [23].…”
Section: Text Mining and Research Area Modellingmentioning
confidence: 99%